Update of the sCO2-test rig at Cranfield University - Anselmi Palma, Eduardo; Belleoud, Pierre; Roumeliotis, Ioannis; Pachidis, Vassilios (American Society of Mechanical Engineers (ASME), 2022)
Since 2018, there is an experimental supercritical carbon dioxide (sCO2) facility operating at Cranfield University. The purpose of this rig is to enable the exploration of supercritical carbon dioxide as a working fluid for future bottoming power cycle applications and, more recently, for thermal management applications. The core of the rig is a transcritical closed loop, which has recently been upgraded. The upgrades include an increase in the number of measurement stations, changes to the types of measurements taken, as well as the addition of a new, dedicated data acquisition system. A summary of some of the lessons learned from different test campaigns conducted from 2018 to 2021 is provided, along with a discussion on the measurement upgrades performed. The experience obtained with this rig, as recounted in this paper, could be relevant to similar test rigs or future power cycles applications.
Keywords: supercritical carbon dioxide; test rig; temperature measurement; thermal management; uncertainties; heat exchanger; waste heat recovery; transcritical CO2 cycle regulation